The first record and occurrence of microsporidian pathogen, Chytridiopsis cf. typographi (Microspora) in Pityokteines curvidens (Coleoptera, Curculionidae) populations in Türkiye - Tuğba Sağlam; Mustafa Yaman (Turkish Journal of Forestry)
Pityokteines curvidens is one of the most damaging bark beetles to coniferous trees, especially fir and it may cause significant tree death in Türkiye. Control methods are insufficient to control the pest due to its biology under tree bark. Entomopathogens can play a suppressive role on natural populations of pest insects. In the present study, the occurrence of Chytridiopsis typographi, the microsporidian pathogen of P. curvidens is presented for the Bolu region during four years. A total of 1.366 P. curvidens adult samples were dissected and searched for the microsporidian pathogen during the study. The first infection was found in P. curvidens adult samples collected in 2009 with a 1.6% infection rate. After 2009, the infection was also observed in the years, 2020 and 2021 as 0.8 and 3.6%, respectively. The infection ranged from 0.8 to 3.6%. The results of our study show that C. typographi has established a relatively stable infection in the P. curvidens populations over the last decade. This is the first study to show the occurrence of an entomopathogenic microsporridium in P. curvidens populations in Türkiye.